An Investigation on the Antioxidant Activities of Hyssopus officinalis L. and Echinacea purpurea L. Plant Extracts in Oil Model System - H Soleimani; M Barzegar; MA Sahari; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2011)
Background: Nowadays, therechr('39')s a growing demand for the natural antioxidants due to the harmful effects of synthetic antioxidants. Therefore, introduction of new natural antioxidants (especially those with plant origin) is very important. Objective: The present study explores the chemical constitution and antioxidant activity of leaf extract of Hyssopus officinalis L. and extract of aerial parts of Echinacea purpurea L., as two valuable natural antioxidants in soybean oil. Methods: Total phenolic content of the water extract of Hyssopus officinalis L. and Echinacea purpurea L. were determined by Folin-Ciocalteu method. The antioxidant activity (AOA) of these two extracts were evaluated with DPPH•, ABTS•+ and beta carotene bleaching (BCB) methods. Furthur, the oven tests including peroxide and thiobarbituric acid values were done at 70º C in soybean oil system. Results: Total phenolic content of Hyssopus officinalis L. and Echinacea purpurea L. were 200 and 60 mg/g phenolic components (galic acid equivalent), respectively. In DPPH• test, EC50 value of Hyssopus officinalis L. and Echinacea purpurea L. were 35.6± 4.7 and 123.0± 10.9 ppm, respectively. In the oven test (in soybean oil), AOA of all concentrations of HOE was comparable to BHT and BHA at the concentration of 100 ppm. AOA of EPE was comparable to BHT at concentrations of 100 and 200 ppm, but lower than that of BHA. Conclusion: In all three DPPH•, ABTS•+ and beta carotene bleaching tests, the antioxidant activity of Hyssopus officinalis extract (HOE) was greater than that of Echinacea purpurea extract (EPE). The antioxidant activity of both extracts improved with increase of the concentration. Further, HOE and EPE were able to reduce the oxidation rate of soybean oil under conditions of the oven test at 70° C. Thus, these two extracts could be appropriate natural alternatives to synthetic antioxidants.